2006
DOI: 10.1016/j.molcel.2005.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Nrd1 Interacts with the Nuclear Exosome for 3′ Processing of RNA Polymerase II Transcripts

Abstract: The exosome complex is involved in multiple RNA processing and degradation pathways. How exosome is recruited to particular RNA substrates and then chooses between RNA processing and degradation modes remains unclear. We find that the RNA binding protein Nrd1, complexed with its partners Nab3, Sen1, and cap binding complex, physically interacts with the nuclear form of exosome. Nrd1 stimulates the RNA degradation activity of the exosome in vitro. However, Nrd1 can also block 3' to 5' degradation by the exosome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
337
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 273 publications
(352 citation statements)
references
References 57 publications
(86 reference statements)
14
337
1
Order By: Relevance
“…Nrd1 (nuclear pre-mRNA down-regulation) is an essential nuclear RNA-binding protein that directs termination of snoRNA and some mRNA transcripts, in association with an interacting protein, the helicase Sen1 (Steinmetz and Brow 1996;Steinmetz et al 2001;Ursic et al 2004;Vasiljeva and Buratowski 2006). Nrd1 contains a CID (Meinhart and Cramer 2004;Meinhart et al 2005) that interacts with CTD phosphorylated at Ser5 (Conrad et al 2000;Gudipati et al 2008;Vasiljeva et al 2008a).…”
Section: The Nrd1 Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…Nrd1 (nuclear pre-mRNA down-regulation) is an essential nuclear RNA-binding protein that directs termination of snoRNA and some mRNA transcripts, in association with an interacting protein, the helicase Sen1 (Steinmetz and Brow 1996;Steinmetz et al 2001;Ursic et al 2004;Vasiljeva and Buratowski 2006). Nrd1 contains a CID (Meinhart and Cramer 2004;Meinhart et al 2005) that interacts with CTD phosphorylated at Ser5 (Conrad et al 2000;Gudipati et al 2008;Vasiljeva et al 2008a).…”
Section: The Nrd1 Complexmentioning
confidence: 99%
“…Nrd1 can also recruit the exosome complex, coupling the Nrd1 termination pathway to exosome-dependent trimming or degradation of transcripts ( Fig. 2; Vasiljeva and Buratowski 2006).…”
Section: The Nrd1 Complexmentioning
confidence: 99%
“…It has recently been shown that the RNA-binding proteins Nrd1 and Nab3 interact with the nuclear exosome and are required for the termination of RNAPII and cryptic unstable transcripts in yeast. [18][19][20] The wide variety of PAR types may in part reflect the diversity of cleavage, elongation, termination, and exosome components that form and interact with the RNAPII complex. Indeed, one of the most appealing aspects of a model of RNAPII-dependent small RNA biogenesis is that it Cell Cycle 2009; Vol.…”
Section: Tirnas In Plants and Nematodesmentioning
confidence: 99%
“…(41/42-like heterodimer) [31] Cofactors for the exosomes without 3¢ exoRNase activity RhlB RNA helicase [50] Degradosome complex in certain bacteria [51] Ski7p and Ski RNA helicase complex [52,53] Mtr4p RNA helicase and TRAMP complex [54], Rrp47 [48], Nrd1 [55] RNA helicase associated with AU-rich element or RHAU [56], KSRP [57], TTP [58] a It is not known yet whether human nuclear and cytoplasmic exosomes contain different components.…”
Section: Chloroplastmentioning
confidence: 99%